Combination of tumor vessel normalization and immune checkpoint blockade for breast cancer treatment via multifunctional nanocomplexes. (21st June 2022) - Zeng, Yingping; Yu, Tong; Zhang, Shufen; Song, Guangtao; Meng, Tingting; Yuan, Hong; Hu, Fuqiang
Abstract : Nanocomplexes which can accurately deliver drugs to tumor tissues and release different drugs at different sites with different rates were prepared to combine tumor vessel normalization with immune checkpoint blockade. Abstract : Tumor vessel normalization can alleviate hypoxia, reduce the intratumoral infiltration of immunosuppressive cells and increase the intratumoral infiltration of immune effector cells (CD8 + T cells), further reversing the immunosuppressive microenvironment. Here, nanocomplexes (lipo/St@FA–COSA/BMS-202) which can accurately deliver drugs to tumor tissues and release different drugs at different sites with different rates were prepared to combine tumor vessel normalization with immune checkpoint blockade. The results of drug release in vitro showed that in a pH 6.5 release medium, lipo/St@FA–COSA/BMS-202 rapidly released the vascular normalizing drug (sunitinib, St) and slowly released the PD-1/PD-L1-blocking drug (BMS-202). The results of in vivo experiments showed that the rapidly released St normalized tumor vessels and formed an immunosupportive microenvironment which improved the anti-tumor efficacy of BMS-202. In conclusion, the drug delivery strategy significantly inhibited tumor growth and had excellent anti-tumor efficacy, which can provide a potential approach for effective tumor treatment.